The effect of calpain inhibitor-I on copper oxide nanoparticle-induced damage and cerebral ischemia-reperfusion in a rat model - Karimkhani, Hadi; Shojaolsadati, Paria; Yiğitbaşı, Türkan; Kolbaşı, Bircan; Emekli, Neslin (My University, 2024)
This study aimed to investigate the effects of the calpain inhibitor N-Acetyl-Leu-Leu-norleucinal (ALLN) on neuroapoptotic cell damage caused by Copper Oxide Nanoparticles (CuO-NP) and exacerbation of damage through brain ischemia/reperfusion (I/R) in a rat model. Male Wistar Albino rats (n=80) were divided into eight groups: Control, I/R, CuO-NP, CuO-NP+I/R, I/R+ALLN, CuO-NP+ALLN, CuO-NP+I/R+ALLN, and DMSO. Biochemical markers (MBP, S100B, NEFL, NSE, BCL-2, Cyt-C, Calpain, TNF-?, Caspase-3, MDA, and CAT) were measured in serum and brain tissue samples. Histological examinations (H&E staining), DNA fragmentation analysis (TUNEL) were performed, along with Caspase-3 assessment. The ALLN-treated groups exhibited significant improvements in biochemical markers and a remarkable reduction in apoptosis compared to the damaged groups (CuO-NP and I/R). H&E and Caspase-3 staining revealed damage-related morphological changes and reduced apoptosis in the ALLN-treated group. However, no differences were observed among the groups with TUNEL staining. The findings suggest that ALLN, as a calpain inhibitor, has potential implications for anti-apoptotic treatment, specifically in mitigating neuroapoptotic cell damage caused by CuO-NP and I/R.
Keywords: Anti-Apoptotic Treatment; Brain İschemia-Reperfusion (I/R); Calpain Inhibitor; Cerebral İschemia-Reperfusion (I/R); Copper Oxide Nanoparticle (Cuo-NP); Rat Model